Effect of lutein supplementation on blood lipids and advanced glycation end products in adults with central obesity: a double-blind randomized controlled trial - Zhou, Juan; Wang, Shanshan; Wang, Qiang; Zhao, Rui; Wang, Dongxia; Xie, Huihui; Du, Yatan; Xu, Yue; Deng, Jin; Huang, Yue; Liu, YuanHua; Peng, Xiaolin; et al. (Food & function, 2025)
Central obesity poses a significant health threat. Lutein-rich fruits and vegetables may help manage obesity. Limited evidence suggests that lutein exerts health effects by inhibiting advanced glycation end products (AGEs), but data on its effects in centrally obese individuals are sparse. Thus, we aimed to investigate the effects of lutein supplementation in subjects with central obesity. A double-blind, randomized controlled trial was conducted involving patients with central obesity. Anthropometric indices, dietary intake, metabolic parameters, carotenoid and AGEs levels were compared between those receiving a 32-week intervention of 10 mg d −1 lutein and a placebo group. There were 117 patients randomly assigned in the analysis. Twenty-three patients were lost to follow-up. Both intention-to-treat analysis and the per-protocol analysis showed significant reductions in plasma total cholesterol, low-density lipoprotein cholesterol, apolipoprotein B, and malonaldehyde levels in the lutein supplementation group compared with the placebo group. Significant differences were also observed between the groups in plasma lutein, carboxyethyl lysine (CEL), carboxymethyl lysine (CML), methylglyoxal hydroimidazolone (MG-HI) levels and skin carotenoid index (all P < 0.05). The mean difference and 95% confidence interval were 0.12 [0.08 to 0.16] μg ml −1 , −8.76 [−16.60 to −0.89] ng ml −1 , −72.3 [−134.0 to −10.9] ng ml −1 , −233.9 [−429.0 to −36.8] ng ml −1 and 0.94 [0.56 to 1.31] a.u., respectively. Furthermore, changes in plasma lutein concentration were positively correlated with changes in the skin carotenoid index ( r = 0.41, P < 0.001), and negatively correlated with changes in plasma CEL ( r = −0.24, P = 0.018), (CML) ( r = −0.21, P = 0.051, and MG-H1) ( r = −0.25, P = 0.017). In conclusion, regular lutein intake can improve metabolic health in adults with central obesity by increasing plasma lutein concentrations, reducing oxidative stress, lowering plasma TC, LDL-C, and ApoB levels, and downregulating AGEs. Regular lutein intake can improve metabolic health in adults with central obesity by increasing plasma lutein concentrations, reducing oxidative stress, lowering plasma TC, LDL-C, and ApoB levels, and downregulating AGEs.